Comparison of endoscopic band ligation and endoclip closure of colonic perforation: Technical feasibility and efficacy in an ex vivo pig model. Issue 5 (31st March 2014) - Lee, Tae Hoon; Han, Joung‐Ho; Jung, Yoonho; Lee, Suck‐Ho; Kim, Dae Hoon; Shin, Ji Yun; Lee, Tae Soo; Kim, Myunghwan; Choi, Seok‐Hwa; Kim, Hyun; Park, Seonmee; Youn, Seijin
<x xml:space="preserve">Abstract</x> Background and Aim Recent reports have indicated several instances of successful treatment of bowel perforation by using endoscopic band ligation (EBL) when treatment with endoclipping is unsuccessful, but this salvage method has not been investigated in any prospective model. Herein we aimed to compare the technical feasibility and efficacy of EBL and endoclip use in intraluminal closure of colon perforation, in an ex vivo model. Methods Standardized colonic perforations were created using fresh porcine colon and subsequently closed by full‐thickness interrupted sutures, endoclip (QuickClip2TM), or EBL. Each closure site was tested with compressed air by using a digital pressure monitor for evaluating leak pressure. Results No significant differences were noted between the endoclip and EBL in leak pressures. Mean (± SD) pressures for air leakage from the perforations closed using the different devices were as follows: normal colon samples, 52.0 ± 13.2 mmHg; perforations closed with hand‐sewn sutures, 32.3 ± 8.3 mmHg; perforations closed with endoclipping, 53.5 ± 22.7 mmHg; and perforations closed with EBL, 50.4 ± 12.5 mmHg. Time taken for closure by EBL was significantly less than that for closure by endoclipping (3.2 ± 1.7 min vs 6.8 ± 1.3 min, P < 0.01). Further, the number of devices used to achieve complete closure in the EBL group was lower than that with endoclipping (1.6 ± 0.5 vs 3.7 ± 0.8, P < 0.01). Conclusion Endoluminal closure of a 1.5‐cm colon perforation with EBL decreased procedure time and was not inferior in leak pressure compared with endoclipping in this ex vivo porcine model.